2012
DOI: 10.1093/icvts/ivs231
|View full text |Cite
|
Sign up to set email alerts
|

Impact of New York Heart Association classification, advanced age and patient-prosthesis mismatch on outcomes in aortic valve replacement surgery

Abstract: OBJECTIVES More elderly patients (>80 years of age) are being referred for aortic valve replacement (AVR) with or without CABG. Current risk stratification models may not accurately predict the preoperative risk in these patients. We sought to determine which perioperative variables were relevant in determining short-term (30-day to in-hospital) outcomes in our intuition's series of consecutive AVR and AVR+CABG surgeries. We constructed a novel variable, patient-prosthesis mismatch (PPM) in the presence of dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
8
1
1
Order By: Relevance
“…Since degenerative aortic stenosis is associated with ageing, the need for aortic valve replacement (AVR) is increasing. 1 Age is no longer a contraindication for AVR via surgical aortic valve replacement (SAVR) or transcutaneous aortic valve replacement (TAVI). 2 Introduction of new knowledge enabling minimally invasive aortic treatments has led to a paradigm shift in cardiac healthcare for the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Since degenerative aortic stenosis is associated with ageing, the need for aortic valve replacement (AVR) is increasing. 1 Age is no longer a contraindication for AVR via surgical aortic valve replacement (SAVR) or transcutaneous aortic valve replacement (TAVI). 2 Introduction of new knowledge enabling minimally invasive aortic treatments has led to a paradigm shift in cardiac healthcare for the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…10 Our recent study on short-term postoperative outcomes and survival further underscores the low rates of mortality and adverse outcomes associated with AVR. 11 These results suggest that not only is AVR safe and effective, even for the very elderly, but that patients can expect favorable outcomes several years after the procedure. Naturally, we sought to investigate the midterm outcomes and survival of our series of AVR patients.…”
Section: Introductionmentioning
confidence: 80%
“…Our previous study and others have shown that AVR is a safe and effective procedure that confers a better quality of life and survival in the short term compared to published data on nonsurgically managed AS patients. [4][5][6][7][8][9]11 The majority of our patients are elderly (>70 years old) and have numerous comorbidities. Thus it is important to examine how age and other factors influence midterm postsurgical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…and Jamieson et al . reported that PPM was related to early mortality after aortic valve replacement [ 15 , 16 ]. Conversely to the decrease in aortic root enlargement operations, this study observed a trend to choose larger aortic valves: size 21 was the one most frequently used in 1999, whereas size 23 was preferred in 2008 ( p < 0.05, Table VI ).…”
Section: Discussionmentioning
confidence: 99%